High-Throughput Sequencing Reveals H2O2 Stress-Associated MicroRNAs and a Potential Regulatory Network in Brachypodium distachyon Seedlings - Lv, Dong-Wen; Zhen, Shoumin; Zhu, Geng-Rui; Bian, Yan-Wei; Chen, Guan-Xing; Han, Cai-Xia; Yu, Zi-Tong; Yan, Yue-Ming (Frontiers in Plant Science, 2016)
Oxidative stress in plants can be triggered by many environmental stress factors, such as drought and salinity. Brachypodium distachyon is a model organism for the study of biofuel plants and crops, such as wheat. Although recent studies have found many oxidative stress response-related proteins, the mechanism of microRNA (miRNA)-mediated oxidative stress response is still unclear. Using next generation high-throughput sequencing technology, the small RNAs were sequenced from the model plant B. distachyon 21 (Bd21) under H2O2 stress and normal growth conditions. In total, 144 known B. distachyon miRNAs and 221 potential new miRNAs were identified. Further analysis of potential new miRNAs suggested that 36 could be clustered into known miRNA families, while the remaining 185 were identified as B. distachyon-specific new miRNAs. Differential analysis of miRNAs from the normal and H2O2 stress libraries identified 31 known and 30 new H2O2 stress responsive miRNAs. The expression patterns of seven representative miRNAs were verified by reverse transcription quantitative polymerase chain reaction (RT-qPCR) analysis, which produced results consistent with those of the deep sequencing method. Moreover, we also performed RT-qPCR analysis to verify the expression levels of 13 target genes and the cleavage site of 5 target genes by known or novel miRNAs were validated experimentally by 5’ RACE. Additionally, a miRNA-mediated gene regulatory network for H2O2 stress response was constructed. Our study identifies a set of H2O2-responsive miRNAs and their target genes and reveals the mechanism of oxidative stress response and defence at the post-transcriptional regulatory level.